Cardiovascular disease and toxic metals - Çomakli, Seli̇m; Sevi̇m, Çi̇ğdem; Doğan, Eli̇f (Elsevier BV, 2020)
Abstract Heavy metal exposure can lead to death and disability. A variety of sources including soil, wastewater, mining activities, industrial waste, sewage wastes, pesticides used in agriculture and automobile exhaust gas contribute to the overall metal burden. The adverse health effects of heavy metals such as lead, arsenic, mercury, and cadmium have become more complicated and challenging for the world owing to the highly complex nature of heavy metal–biological interactions. Although the mechanism of action of metals varies, the only way to help the body struggle with the heavy metal burden is to remove heavy metals from the body and eliminate, or reduce, the possibility of re-exposure. It is thought that the use of biomarkers to detect early damage to the cardiovascular system by exposure to low amounts of heavy metals may be beneficial. Furthermore, the clinical status for the patient can be questioned by determining long-term low levels of exposure to humans for doses empirically used to induce cardiotoxicity.
Keywords: 13. Climate action; 3. Good health